GENDER DIFFERENCES ON THE ATTITUDES OF PHILIPPINE NORMAL UNIVERSITY COLLEGE STUDENTS TOWARDS DANCING - Randyll V Villones (Program Pascasarjana Universitas Negeri Jakarta, 2015)
Gender differences and the attitudes of students towards physical activities are at times used as measures or determinants in the effectiveness and success of teaching dance as one of the many activities in Physical Education program which was found out to be beneficial to students ’ total development; physically, emotionally, mentally and socially. Hence, the belief on female dominance and stereotyping associated with dance, created a stigma among male students to engage in any dance program. The study identifies the current status of the respondents’ attitude towards dancing with emphasis on specifying the significant differences on the variables associated to the attitudes of the respondents. The descriptive method of research was employed using two hundred forty nine (249) second year College students consisted of one hundred ninety two (192) female and fifty seven (57) male students. The data in this study were obtained using a researcher-made questionnaire patterned after the Modified Fennema-Sherman questionnaire which underwent validation before its utilization.The mean and t- test used to analyze the collected data and findings revealed that differences in the attitudes of both male and female in terms of perception on teacher’s attitude, personal confidence about the subject matter, and the usefulness of the subject content were found not significant except on the subject perceived as a female domain. The conclusions and recommendations based on these findings were identified and discussed.